PENGARUH PELATIHAN AKUNTANSI, DAN LAMA USAHA TERHADAP PERENCANAAN DAN PENGGUNA INFORMASI AKUNTANSI PADA UMKM KECAMATAN LOWOKWARU KOTA MALANG - Ayu Krisnawati; Linda Wahyu Widiastuti; Justita Dura; Mochamad Renaldi (RISTANSI: Riset Akuntansi, 2023)
To determine the effect of accounting training, and length of business on the planning and use of accounting information in MSMEs in Lowokwaru sub-district, Malang City. The sampling technique was by distributing questionnaires, with a total sample of 97 respondents. The research method used is quantitative. with the help of the SPSS 25 application. The results showed that accounting training and length of business had an influence on the planning and use of accounting information in Lowokwaru District, Malang City. Future research is expected to use a broader and more comprehensive research sample.